Vascular access parameters among prevalent dialysis patients: a single center survey (BIRDEM Medical Journal, 2020)
Background: Vascular access is one of the most important outcome determinant of patients on hemodialysis. In Bangladesh increasingly more patients are started on hemodialysis as a lifesaving procedure. But we lack organized data on different aspects of dialysis practice. Data related to vascular access is even more scanty.Method: A survey was undertaken in one of the busy dialysis centers in Dhaka with a large number of patients on maintenance hemodialysis .Data were collected by doctors in dialysis units from patients along with records kept in the dialysis unit during November and December 2017.Results: Total 143 patients were included. 53% of these patients belonged to age group 61 to 80 years, 39% to age group 41 to 60 years; 56.6 % female and 43.4% male. 73.4% of the study patients received dialysis via central venous catheter at the initiation. But among the prevalent patients during study period, 84% patient were receiving dialysis via arterio-venous fistula and 5% via arterio-venous graft as permanent vascular access. Among these permanent vascular access left forearm was used in 47% and left upper arm in 33% of cases. Vascular ultrasound mapping before permanent access creation was done in only about 40% of cases. Almost 56 % of the vascular access surgery was done by experienced medical graduates in vascular access creation without any post graduate surgical qualifications.Conclusion: Vascular access data should be collected in a structured manner so that dialysis practice pattern of different centers and regions of the country can be compared. Similar data from several centers around the country will increase scope of improvement .Birdem Med J 2020; 10(2): 120-124